A self-paced online emotion socialization intervention for parents of children with challenging behavior: Tuning in to Kids OnLine - Havighurst, Sophie S.; Mangelsdorf, Shaminka N.; Boswell, Nikki; Little, Jonathon; Zhang, Abby; Gleeson, Kate; Hussain, Aniqa; Harley, Ann; Radovini, Alessandra; Kehoe, Christiane E. (Frontiers in Psychology, 2024)
Evidence-based parenting programs delivered using online technology are an important way to enhance program uptake. To date, programs that address emotion socialization processes, such as Tuning in to Kids, have always been delivered in person, via group or one-to-one delivery. This study used a randomized control design to examine the efficacy of the self-paced Tuning in to Kids OnLine (TIKOL). Participants were 150 parents of children aged 4-10 years old with challenging behaviors, randomized into intervention or 10-month waitlist control. Parents and teachers completed questionnaires at baseline and 6 months after the intervention (equivalent time points for controls) measuring parent wellbeing, parent emotion socialization, parent efficacy, child behavior and anxiety. Analyses, using mixed methods multilevel modelling, showed that intervention parents reported significantly reduced emotion dismissiveness and increased emotion coaching, empathy and efficacy compared to controls who did not. Parents participating in TIKOL also reported that their children’s behavior problems and anxiety were significantly improved. Greater engagement (modules watched and duration of support calls) was associated with more significant improvements. Findings provide preliminary support for the efficacy of TIKOL in improving parents’ emotion socialization and reducing child behavior problems and anxiety, especially when efforts to support online engagement are utilized. Further evaluation using independent observations and a sample representing a wider demographic would strengthen these findings.